Decolourization of emulsion paint industry wastewater by a combination of chemical coagulation and fenton's reagent / Nurul Azlin Bestho - Bestho, Nurul Azlin (Faculty of Applied Sciences, 2009)
This study carried out to examine the efficiency of chemical coagulation combined with Fenton's reagent for decolourization of wastewater from the emulsion paint manufacturing industry. Parameters to chemical coagulation for both samples, such as the pH and dosages of coagulant and flocculant were determined by using qualitative analysis of jar test experiments. 0.12% alum and 0.01% CaC03 were the optimum parameters for coagulation of both samples. The optimum pH for chemical coagulation was in the range of 4.24 - 4.32. From Fenton's oxidation, the optimum conditions were found to be at pH 3.4, 0.09 mg/L Fe2* and 0.02 mg/L H2O2* The corresponding COD and colour removals were 86.5% and 42.2%, respectively. The wastewater was finally treated by a combination of chemical coagulation and Fenton's reagent. The corresponding results of COD and colour removals were 93% and 83.7%, respectively.